Exploring the influence of entrepreneurial orientation on firm performance: Absorptive capacity in family-owned food and beverage enterprises - Marchyta, Nony Kezia; Wijaya, Evan; Susilo, Clarissa Listya (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2025)
Growth in Indonesia’s food and beverage industry is primarily dominated by family companies that contribute significantly to Gross Domestic Gross. The food and beverage industry is predicted to be one of the sectors with the most dynamic growth. The importance of the performance of family companies engaged in the food and beverage sector in Indonesia and previous research gaps are the reasons for researching and examining the effect of entrepreneurial orientation on firm performance with absorptive capacity as a mediating variable. This research is a quantitative study with a sample of 120 family companies engaged in Indonesia’s food and beverage sector, especially in the Jakarta, Surabaya, and Sulawesi regions. Data on research respondents were obtained by distributing research questionnaires through social media or visiting research respondents directly. The data obtained was then analyzed using the Structural Equation Model - Partial Least Square. The results obtained are entrepreneurial orientation positively affects firm performance, entrepreneurial orientation affects absorptive capacity, and absorptive capacity affects firm performance. The role of absorptive as mediation enables the transformation of entrepreneurial orientation to firm performance. Family firms must integrate knowledge and create new capabilities aligned with the knowledge-based view.